A rare case of unilateral eosinophilic fasciitis associated with ipsilateral extragenital lichen sclerosus - Aseem Sharma; Rahul Ray; Jandhyala Sridhar; Arti Trehan; Manish Khandare (Wolters Kluwer Medknow Publications, 2016)
Eosinophilic fasciitis, also known as Shulman's syndrome, is a fibrosing scleroderma-like syndrome, which is a distinct entity. A 55-year-old man, presented with progressive skin darkening, thickening, and tightening over the left lower limb since 6 months. Dermatological examination revealed a hyperpigmented indurated area on the left thigh, extending to the anterior aspect of the left leg. A well-defined hypopigmented indurated plaque was present over the left iliac region. Histopathology and imaging studies confirmed the diagnosis of eosinophilic fasciitis and lichen sclerosus. The indurated lesion on the left lower limb responded dramatically well to oral corticosteroids. This is a rare case of unilateral eosinophilic fasciitis associated with ipsilateral extragenital lichen sclerosus.